Hadith Learning Strategies in Early Childhood Education - Moh. Rofiki; Nadrah Nadrah; Cahyo Hasanudin; Suttrisno Suttrisno; Rizki Ananda; Kevin William Andri Siahaan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
There are two schools that carry out hadith learning in PAUD, namely PAUD RA Al Falah and PAUD Barokah in Pematangsiantar City. The Hadith learning education program delivered at RA Al Falah PAUD aims to shape and mold the personality of early childhood based on Faith and Piety, while the Hadith learning education program delivered at Barokah PAUD aims to form a generation with the character of the Prophet who has noble and noble character. character building. The purpose of this study was to determine learning strategies in PAUD. This study uses a descriptive qualitative approach with a multi-site design with data collection through interviews, observation and documentation. These stages include reduction, presentation and conclusion with research conducted on the RA Al Falah Al-Qur'an PAUD Program and the Barokah PAUD Program in Pematangsiantar City. The results of the research obtained by the RA Al Falah Qur'an PAUD Program and the Barokah PAUD Program Pematangsiantar City were the implementation of hadith learning strategies every day after reading prayers, reading Asmaul Husna, short suras. The conclusion of this research is the implementation strategy of developing aspects of child development through hadith learning, which is carried out classically and individually has been considered successful; its implementation is considered successful, and the results are also very good because friendly character education in all its aspects has improved significantly.